Money meanings among French and American adolescents. Issue 5 (8th August 2016) - Rose, Gregory; Bakir, Aysen; Gentina, Elodie
Abstract : Purpose: This study examines adolescent' money attitudes in the U.S. and France. It introduces and validates an 18-item scale for assessing adolescent money attitudes, explores the symbolic values that American and French teens attach to money, identifies the major segments of teens based on their attitudes toward money, and assesses the importance that these groups place on price, novelty, and brand name. Design/methodology/approach: Twenty-eight in-depth interviews were initially conducted to explore adolescent' money attitudes, assist in the development of measures, and provide a context for interpreting subsequent results. Exploratory factor analysis (among 90 French and 70 American adolescents), followed by confirmatory factor analysis (among 332 French and 273 American adolescents) indicated that six dimensions captured money meanings. These dimensions were utilized in a subsequent cluster analysis to group teens into segments. Findings: Six dimensions (worry, achievement, status, security, budget, and evil) captured teenage money attitudes among French and American adolescents. A cluster analysis based on these dimensions yielded three groups: no worries, success, and security. These three groups varied in their attitudes toward money and the importance that they placed on price, brand, and novelty in purchasing. Practical implications: This study provides measures for assessing adolescent money meanings, and presents a preliminary segmentation of U.S. and French adolescents based on their attitudes toward money. Originality/value: The results demonstrate the impact of money attitudes on adolescent consumption preferences, demonstrate the utility of measuring adolescent' money attitudes and segmenting adolescents based on these attitudes, and emphasize the importance of both cultural and individual differences.